Factors Determining Postoperative Ileus After Surgery for Colon Cancer: Comparison of Right- and Left-Sided Resections - Adamova, Zuzana; Filova, Michaela; Slovacek, Radim (Surgical technology international, 2022)
INTRODUCTION: The passage of flatus and stool, as well as tolerating a solid diet, represents a crucial moment in recovery after colonic resections. The present study compares functional recovery after left and right colectomies for colon cancer. MATERIALS AND METHODS: This is a retrospective analysis. Consecutive patients with elective left and right colon resections were examined. Primary analysis compared time to first bowel motion and development of postoperative ileus. Secondary analyses tried to define risk factors for prolonged restoration of bowel function in right- and left-sided resection groups. RESULTS: In total, 147 patients were included. While laparoscopic approach was preferred for both sides (87% vs. 87%; p=0.496), left colectomies took longer (183 vs. 153 min; p=0.012), the lymph node harvest was smaller (16 vs. 20; p=0.005), and there was an increased need for perioperative fluids (4451 vs. 4039ml; p=0.006). Epidural use, postoperative potassium level, and glycemia were similar. Also, no significant differences were observed for complications and length of stay. First flatus was observed at postoperative day 1, 9 (left), and 2.5 (right), respectively (p=0.002). There was no significant difference in passage of first stool and intake of first solid food. Twenty-seven patients (35%) needed a postoperative nasogastric tube after right colectomy compared to 11 patients (16%) after left colectomy (p=0.012). Right-sided colectomies required the tube for longer (6.1 vs. 3.4; p=0.005). CONCLUSIONS: Postoperative ileus was more frequent after right-sided colectomies despite shorter operative time. The reason for this finding is currently unknown and deserves further attention. For the time being, we can just be more cautious with early feeding after right colectomy.
Keywords: Laparoscopy; výsledek terapie; Colectomy; nádory tračníku; laparoskopie; lidé; ileus; pooperační komplikace; Treatment Outcome; kolektomie; délka pobytu; Length of Stay; Colonic Neoplasms; retrospektivní studie; Postoperative Complications; Flatulence; flatulence; Ileus; Retrospective Studies; Humans